‘Melabuh Anjung’: Signification of Cosmological Belief in Developing Traditional Theatre Identity of Sabah East coast - Sharifuddin Zainal; Mohd Kipli Abdul Rahman; Mohamad Azizul Ibrahim (2018)
‘Melabuh Ajung’ is a traditional practice of offering food to the Gods by Sabah East coast ethnic. The term of ‘melabuh ajung’ refers to the practice food offering to the guardians and ancestral spirits. The ‘Ajung’ or boat is sailed into the open water in the ritual to ensure that illnesses and disasters encountered can be treated. ‘Melabuh ajung’ is a practice that closely associated with the healing rituals in traditional belief that is related to their environments. Hence the practice has become a very important tradition and is observed with great reverence of propriety according to customs. However, this practice has significantly decreased due to modernization, changes in life style and the beliefs of the ethnic communities. Although, Sabah is a state of multi-ethnic society rich in cultural diversity and beliefs; Sabah traditional theater is often left behind in the study of traditional performances in Malaysia. The practice of ritual performances as a traditional theater; the performance structures; the aesthetic values and the identity reflected in these performances are more than enough to establish the presence of Sabah traditional theater. Through an ethnographic approach, this paper will reveal the relationship between the Sabah east coast ethnic communities belief- towards the elements of their cosmic spaces using the ‘Melabuh Ajung’ ritual practice as an example of Sabah traditional theatre performance.